Sovereignty vs Human Rights: Legal Conflicts on Global Stage - Shakoor, Usama (Law and Policy Review, 2024)
The following research analyzes the conflict between the sovereignty of a state and the human rights of citizens. These two terms often clash within international law and politics because they severely affect nations all over the world. The article examines the effectiveness of human rights, and extent to which it is implemented in the legal and political frameworks of nations. It also discusses the major differences in policies between developing countries and underdeveloped countries and concludes that certain nations prioritize sovereignty over human rights and vice versa. The research uses a qualitative case study approach to analyze the imbalance between sovereignty and human rights in some regions. The article uses the case studies of Palestinians, Kashmiris, and Uyghur Muslims in China to highlight the ongoing conflicts in these regions to analyze the relationship between the states’ right to self-governance and human rights. It aims to understand the conflict on a deeper global level by comparing these cases. It also discusses the legal frameworks related to the cases. It identifies the role of international organizations and recommendations for the international community in resolving conflicts that arise due to a clash between state sovereignty and human rights. The comparative analysis of the case studies reveals that the implementation and enforcement of human rights are affected by the political, economic, or geographical interests of nations and possibly organizations that are meant to protect human rights. The study recommends changes in international frameworks to ensure the protection of human rights as well as balance them with the state sovereignty of the conflicted nations.